Medical Staff as Catalysts for Change: A Systematic Review on Improving Clinical Environments for Better Care - alali, fatimah mohammed ali; Alammari, Naif Abdulrahman Abkar; Alessa, Zahra Habib; Aldhaif, Noah Ali; Alnahwi, Mohammed Hussain; alfraij, Fatimah abdulaziz saleh; ALMOBARAK, Narjis ibrheem mansor; ALDawood, Balqees Mohammed Ahmed; Alsaleh, Aqeala Taher Habeeb; Alshwai, Khadeajah Ahmed (Journal of Ecohumanism, 2024)
The clinical environment is a critical determinant of healthcare quality and patient outcomes. Medical staff, encompassing physicians, nurses, and allied health professionals, play a pivotal role in catalyzing changes that improve these environments. This systematic review explores the contributions of medical staff as change agents in clinical settings, focusing on their leadership, communication, and training efforts. Following PRISMA guidelines, the review synthesizes evidence from studies published since 2016, highlighting the impact of these interventions on workflow efficiency, resource management, patient safety, and satisfaction. The findings reveal that proactive engagement of medical staff leads to significant enhancements in operational effectiveness and care delivery. Recommendations are provided to support their roles through targeted training programs, policy adjustments, and collaborative initiatives. This review underscores the importance of empowering medical staff to drive sustainable improvements in clinical environments, ultimately fostering better healthcare outcomes.